Implementation of Common European Framework of Reference for Languages-Aligned Assessment in Malaysian Secondary Schools - Azli Bin Affendy Lee , Noor; Akmar Binti Mohd Kasim , Aini (International Journal of Psychosocial Rehabilitation, 2020)
The execution of the Malaysian Education Blueprint 2013-2025 has created several curriculum reforms in the Malaysian ESL (English as a Second Language) syllabus, teaching and assessment. With the adaptation and implementation of the Common European Framework of Reference for Languages (CEFR), starting with primary one and secondary one in Malaysian schools in 2016, this action-oriented approach warranted a degree of essential changes in teaching, learning and assessment in the English classrooms. Therefore, the main aim of this preliminary study was to investigate the views of English teachers on the implementation of the CEFRaligned assessments in the ESL secondary school classroom. It also explored the challenges encountered by teachers in view of the adoption of CEFR onto the lower secondary form English syllabus and assessment. Data were collected via google form questionnaires from English teachers in schools located throughout Malaysia via random convenient sampling. The initial findings revealed that the implementation of CEFR-aligned syllabus and assessments are still divisive among Malaysian ESL school teachers. Most of the English teachers had sufficient knowledge about the revised CEFR-aligned ESL curriculum and how it affects students but find designing CEFRaligned assessments based on the descriptors challenging even after it has been implemented for two years. This resulted in several difficulties faced when incorporating CEFR in their teaching and assessment. In formative assessments, teachers provide sufficient variety of feedbacks but face time constraint issues related to extra administrative duties, heavy workload, school events, and heavy syllabus content. These are the main factors that pose as the main challenges against the effective implementation of the CEFR-aligned assessment. Therefore, to ensure smoother implementation of CEFR in ESL classrooms, all stakeholders need to work together to iron out any issues faced by teachers. Furthermore, a clearer CEFR-aligned assessment guide needed to be developed and added into the syllabus to sufficiently assist ESL teachers in teaching and assessment in Malaysian school.